The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.9734/jenrr/2020/v5i130140
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Biogas and Methane Yields from Different Sizes of Groundnut Shell in a Batch Reactor at Mesophilic Temperature

Abstract: Aim: To study the effects of different sizes of groundnut shell on biogas and methane yields using batch reactor at mesophilic temperature. Place and Duration of Study: The laboratory experiment was carried out at the Laboratory of the Department of Agricultural Engineering, Ladoke Akintola University of Technology, Ogbomoso, Nigeria, between August and October, 2018. Methodology: Batch experiment was set up for a period of 35 days with substrate reduced to 2, 4 and 6 mm sizes. The digesters were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Hydrolysis is perceived to be the rate-limiting stage in the process because of the substrate resistance to the enzymatic attack of the microorganisms due to their structural arrangements (Olatunji et al, 2021). This hydrolysis stage can be improved by applying pretreatment methods such as mechanical, chemical and biological pretreatments (Jekayinfa et al, 2020; Karuppiah and Ebenezer Azariah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis is perceived to be the rate-limiting stage in the process because of the substrate resistance to the enzymatic attack of the microorganisms due to their structural arrangements (Olatunji et al, 2021). This hydrolysis stage can be improved by applying pretreatment methods such as mechanical, chemical and biological pretreatments (Jekayinfa et al, 2020; Karuppiah and Ebenezer Azariah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, it does not for lignocellulose materials like rice straw and maize stalk (Menardo et al, 2012). In line with this assertion, groundnut shell has been established as a lignocellulose material that particle size reduction beyond a particular size does not favour its biogas and methane yields (Jekayinfa et al, 2020). This agrees with what was earlier noticed: if the substrate can be reduced to a point at which it is easy to degrade, overloading of digesters is possible with high organic loading, especially in the batch system.…”
Section: Discussionmentioning
confidence: 96%
“…Another similar research reported that the biogas and methane yields were enhanced until the particle size was 6 mm, but below 6 mm particle size, the yield started to reduce ( Herrmann et al, 2012 ). Jekayinfa et al (2020) reported 6 mm particle size as the optimum value for fresh biogas and methane yields of lignocellulose material. This result also supports what was reported by an earlier researcher when particle size was considered ( Olatunji et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations